UJI KUERSETIN PADA EKSTRAK ETANOL LIDAH BUAYA (ALOE VERA BARBADENSIS) DENGAN METODE KROMATOGRAFI LAPIS TIPIS - Nadia Purnama Dewi; Ade Teti Vani; Dessy Abdullah; Meta Oktora; Fadilla Marisa (Nusantara Hasana Berdikari, 2022)
Aloe vera is a plant of the Liliaceae group. Aloe Barbadensis contains secondary metabolites that function as plant protection against pests and diseases. The grouping of secondary metabolites is known as phytochemical screening. Thin-layer chromatography (TLC) analysis is needed to isolate and identify the components of the secondary metabolites. Method: This is an experimental laboratory. The population was the Aloe Vera Barbadensis Millier species from Kalimantan, obtained from the Lubuk Minturun Agricultural Vocational School. The research process includes sample preparation, maceration extraction with 70% ethanol, flavonoid phytochemical test, and TLC test with kuersetin as a comparison. Result:, A phytochemical test, TLC test with three variations of eluent, namely Methanol: Aquadest (6:4), Butanol: Glacial Acetic Acid: Water (4:1:5). Conclusions: Aloe vera from Lubuk was positive for flavonoid.